Control of Moniliophthora roreri Cif & Par in cocoa using Trichoderma asperellum, ozonated sunflower oil and sacha inchi oil - Sanmiguel Chimbo, Josue David (2025)
In Ecuador, cocoa plantations in Kichwa communities and communes have a high incidence and severity of moniliasis, with production losses ranging from 40 % to 80 % of the annual cocoa harvest. The objective of the research was to evaluate the effect of the application of biological fungicides on Moniliophthora roreri Cif & Par in the crop Theobroma cacao L. Four products were evaluated: Trichoderma asperellum (T1: 2x106 CFU and T5: 2x107 CFU), ozonated sunflower oil (T2: 2,5 mL L-1 and T6: 5 mL L-1), sacha inchi oil (T3: 2,5 mL L-1 and T7: 5 mL L-1) and copper sulfate pentahydrate 270 g L-1 (T4: 1,5 mL L-1 and T8: 2,5 mL L-1), in addition to the absolute control (T9). The trial showed an average of 39,71 % damage by moniliasis. Applications were made every 15 and 22 days, with monitored every 15 days for 9 weeks. The results showed that the treatments had an effect on the level of control of moniliasis in CCN51 cocoa plants, with an average incidence reduction of 38,53 % and severity of 49,73 % compared to that of the absolute control. In addition, values higher than 48 % of efficacy in the control of the phytopathogen were obtained for treatments T8 (51,69 %), T6 (49,36 %), and T2 (48,19 %). Applying ozonated sunflower oil in doses of 2,5 mL L-1 every 15 days and 5 mL L-1 every 21 days is recommended.